1988
DOI: 10.1017/s0007485300013043
|View full text |Cite
|
Sign up to set email alerts
|

Identification of components of cattle urine attractive to tsetse flies, Glossina spp. (Diptera: Glossinidae)

Abstract: The attractiveness of cattle urine to Glossina morsitans morsitans Westwood and G. pallidipes Austen was shown to be entirely attributable to the phenolic components which it contains. Four of the eight naturally occurring phenol derivatives (3- and 4-methylphenol, 3-ethylphenol and 3-n-propylphenol) were electroantennographically active, induced upwind flight in wind-tunnel bioassays and increased trap catches in field tests in Zimbabwe. One of the minor components, 2-methoxyphenol, had little antennographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 15 publications
2
106
1
Order By: Relevance
“…Phenols, formed in Table 2 Behavioural responses of G. brevipalpis in the wind tunnel to acetone alone, to mixtures of acetone plus single carboxylic acid chemostimulants detected in rumen Xuid odour, and to a ternary mixture of 3-n-propyl phenol, 1-octen-3-ol and p-cresol accompanied or not by acetone a a Tests with G. brevipalpis to acetone (A), carboxylic acids detected in rumen Xuid odour, i.e. isobutanoic acid (2MeC3ac), butanoic acid (C4ac), isovaleric acid (3MeC4ac), valeric acid (C5ac), hexanoic acid (C6ac), cyclohexane carboxylic acid (cC6ac) and a mixture of 3-n-propyl phenol, 1-octen-3-ol and p-cresol (POC) at a ratio 1:4:8 released from a polyethylene sachet Asterisks indicate that the percentage response is signiWcantly diVerent from that of the blank control at * P < 0.05; ** 0.01; *** 0.001 levels of probability using Fisher's exact test The release rate of acetone presented neat in a gas-wash bottle and of diVerent carboxylic acids as dispersed from polyethylene sachet was estimated in the plume to 2.67 g/l A, 0.26 g/l 2MeC3ac, 0.51 g/l C4ac, 0.19 g/l 3MeC4ac, 0.38 g/l C5ac, 0.29 g/l C6ac and 0.06 g/l cC6ac (Okech and Hassanali 1990), were found to be the key compounds in urine to elicit attraction of morsitans and the palpalis group tsetse Xies to this substrate (Bursell et al 1988;Filledier and Mérot 1989). In particular, p-cresol and 3-n-propyl phenol were isolated from a bovine urine phenolic fraction and reproduced the attractive power of the mixture of phenols isolated from urine (Bursell et al 1988).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Phenols, formed in Table 2 Behavioural responses of G. brevipalpis in the wind tunnel to acetone alone, to mixtures of acetone plus single carboxylic acid chemostimulants detected in rumen Xuid odour, and to a ternary mixture of 3-n-propyl phenol, 1-octen-3-ol and p-cresol accompanied or not by acetone a a Tests with G. brevipalpis to acetone (A), carboxylic acids detected in rumen Xuid odour, i.e. isobutanoic acid (2MeC3ac), butanoic acid (C4ac), isovaleric acid (3MeC4ac), valeric acid (C5ac), hexanoic acid (C6ac), cyclohexane carboxylic acid (cC6ac) and a mixture of 3-n-propyl phenol, 1-octen-3-ol and p-cresol (POC) at a ratio 1:4:8 released from a polyethylene sachet Asterisks indicate that the percentage response is signiWcantly diVerent from that of the blank control at * P < 0.05; ** 0.01; *** 0.001 levels of probability using Fisher's exact test The release rate of acetone presented neat in a gas-wash bottle and of diVerent carboxylic acids as dispersed from polyethylene sachet was estimated in the plume to 2.67 g/l A, 0.26 g/l 2MeC3ac, 0.51 g/l C4ac, 0.19 g/l 3MeC4ac, 0.38 g/l C5ac, 0.29 g/l C6ac and 0.06 g/l cC6ac (Okech and Hassanali 1990), were found to be the key compounds in urine to elicit attraction of morsitans and the palpalis group tsetse Xies to this substrate (Bursell et al 1988;Filledier and Mérot 1989). In particular, p-cresol and 3-n-propyl phenol were isolated from a bovine urine phenolic fraction and reproduced the attractive power of the mixture of phenols isolated from urine (Bursell et al 1988).…”
Section: Discussionmentioning
confidence: 95%
“…isobutanoic acid (2MeC3ac), butanoic acid (C4ac), isovaleric acid (3MeC4ac), valeric acid (C5ac), hexanoic acid (C6ac), cyclohexane carboxylic acid (cC6ac) and a mixture of 3-n-propyl phenol, 1-octen-3-ol and p-cresol (POC) at a ratio 1:4:8 released from a polyethylene sachet Asterisks indicate that the percentage response is signiWcantly diVerent from that of the blank control at * P < 0.05; ** 0.01; *** 0.001 levels of probability using Fisher's exact test The release rate of acetone presented neat in a gas-wash bottle and of diVerent carboxylic acids as dispersed from polyethylene sachet was estimated in the plume to 2.67 g/l A, 0.26 g/l 2MeC3ac, 0.51 g/l C4ac, 0.19 g/l 3MeC4ac, 0.38 g/l C5ac, 0.29 g/l C6ac and 0.06 g/l cC6ac (Okech and Hassanali 1990), were found to be the key compounds in urine to elicit attraction of morsitans and the palpalis group tsetse Xies to this substrate (Bursell et al 1988;Filledier and Mérot 1989). In particular, p-cresol and 3-n-propyl phenol were isolated from a bovine urine phenolic fraction and reproduced the attractive power of the mixture of phenols isolated from urine (Bursell et al 1988). p-Cresol is currently used in combination to 3-n-propyl phenol, 1-octen-3-ol and acetone to bait visual traps and targets for tsetse Xies Filledier and Mérot 1989;Kappmeier and Nevill 1999) as well as for other haematophagous Xies such as S. calcitrans (Cilek 1999).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, we have also found b-caryophyllene in the breath of cattle (unpublished data from this laboratory). Furthermore, phenols similar to the aromatic chemostimuli 3-and 4-ethyl phenol and 4-ethyl acetophenone of L. camara have already been implicated in the attraction of tsetse flies to animal excreta (Bursell et al, 1988). It would appear that these flies, like other haematophagous arthropods, make parsimonious use of volatile chemostimuli by responding to a set of host volatiles when hungry and to a second-not quite unrelatedset from plants when replete.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds present in aged cattle urine have played a significant role in control strategies of tsetse flies (Vale and Torr 2004). Presented as blends at natural release rates, these compounds increase the trap catch of tsetse flies compared to individual compounds (Bursell et al 1988;Vale et al 1988). Our study showed that phenol, 3-ethylphenol, 4-ethylphenol, 3-methylphenol, and 4-methylphenol, when released within their natural concentration range (Torr et al 1995), and in combination with CO2, attract C. nubeculosus.…”
Section: Behavioral Assaymentioning
confidence: 99%